LESBIAN, GAY, BISEKSUAL, TRANSGENDER PERSPEKTIF AL-QUR’AN DAN HAK ASASI MANUSIA - Neny Muthi'atul Awwaliyah (el-'Umdah, 2021)
LGBT is still a hot polemic in the wider community. Of course we do not want this polemic to be a commotion, an inconvenience and mutual suspicion. The upheaval of thought between the pro and the contra happened around the issue. some of them support it and some are violently rejecting the community. And this caused disputes among scholars, academics, and the wider community. The view of differences in sexual orientation and gender identity outside the relationship between men and women is still very taboo and is still a debate. From the case the author wants to explore more about the LGBT perspective of the United Nations version and the Human Rights.